Opacification of intraocular lens: A rare misdiagnosed postoperative façade - Niranjan Karthik Senthil Kumar (TNOA Journal of Ophthalmic Science and Research, 2021)
Intraocular lens (IOL) opacification can be one of the rare differential diagnoses for delayed decrease in postoperative vision in patients undergoing cataract surgery. A 73-year-old female presented with the complaints of diminished vision in her operated eye 4 years after a surgery for her cataract. After meticulous evaluation, the patient was diagnosed with opacification of IOL, and appropriate IOL exchange was done. The patient regained vision to 6/12. Hence, it is crucial to keep this cause of postoperative decrease in vision and manage accordingly to restore useful vision.